2022
DOI: 10.3389/fmed.2022.929408
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of myocardial injury and mid-regional proAdrenomedullin elevation in determining clinical outcomes of SARS-CoV-2 patients

Abstract: ObjectiveCoronavirus disease 2019 (COVID-19) is a systemic disease induced by SARS-CoV-2 causing myocardial injury. To date, there are few data on the correlation between mid-regional proAdrenomedullin (MR-proADM) and myocardial injury. The aim of this study was to evaluate whether the association of myocardial injury and elevated mid-regional proAdrenomedullin values could predict mortality of SARS-CoV-2 patients, to offer the best management to COVID-19 patients.Materials and methodsAll patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have proposed that virus-induced endothelial dysfunction and damage, resulting in impaired vascular blood flow, coagulation and leakage, may partially explain the development of organ dysfunction [ 74 , 75 ]. Another study showed that myocardial injury induced by SARS-CoV-2 is strongly associated with high MR-proADM values and mortality [ 76 ]. The assessment of MR-proADM may provide vital information to explain the pathophysiological mechanisms of vascular endothelial injury and subsequent organ dysfunction in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed that virus-induced endothelial dysfunction and damage, resulting in impaired vascular blood flow, coagulation and leakage, may partially explain the development of organ dysfunction [ 74 , 75 ]. Another study showed that myocardial injury induced by SARS-CoV-2 is strongly associated with high MR-proADM values and mortality [ 76 ]. The assessment of MR-proADM may provide vital information to explain the pathophysiological mechanisms of vascular endothelial injury and subsequent organ dysfunction in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is due to hypoxia inducing a reduced oxygen supply to the heart, causing a modest or massive elevation in troponin concentration, which is not necessarily related to the deterioration of systolic left ventricular function in left ventricular overload secondary to parenchymal or vascular disease of the lung resulting in subendocardial damage of the right ventricular myocardium in 19% of cases and by cytokine-induced injury [ 177 , 178 , 182 , 183 , 184 , 185 , 186 ]. Myocardial injury can be caused through one of three mechanisms: myocyte stretching, myocardial damage, or oxidative stress [ 187 ]. The MR-proADM biomarker indicates cardiovascular stress [ 187 , 188 ].…”
Section: Role Of Adrenomedullin Expression In Infective Acute Cardiac...mentioning
confidence: 99%
“…ADM is a peptide of 52 amino acids, a member of the CT/CGRP superfamily whose gene is located on the 11 chromosome. It expresses the onset of organ damage, its severity, the degree of edema and prognosis [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The precursor peptide, mid-regional pro-adrenomedullin (MR-proADM), is more stable than ADM, released in 1:1 ratio to ADM. MR-proADM shows high predictiveness regarding prognosis during severe inflammation, such as in the case of sepsis, acute heart failure (AHF) or COVID-19 [8][9][10][11][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation